Addressing Cancer Disparities Among American Indians through Innovative Technologies and Patient Navigation: The Walking Forward Experience - Petereit, Daniel G.; Guadagnolo, B. A.; Wong, Rosemary; Coleman, C. N. (Frontiers in Oncology, 2011)
Purpose/Objective(s): American Indians (AIs) present with more advanced stages of cancer and, therefore, suffer from higher cancer mortality rates compared to non-AIs. Under the National Cancer Institute (NCI) Cancer Disparities Research Partnership (CDRP) Program, we have been researching methods of improving cancer treatment and outcomes since 2002, for AIs in Western South Dakota, through the Walking Forward (WF) Program. Materials/Methods: This program consists of (a) a culturally tailored patient navigation program that facilitated access to innovative clinical trials in conjunction with a comprehensive educational program encouraging screening and early detection, (b), surveys to evaluate barriers to access, (c) clinical trials focusing on reducing treatment length to facilitate enhanced participation using brachytherapy and intensity modulated radiotherapy (IMRT) for breast and prostate cancer, as AIs live a median of 140 miles from the cancer center, and (d) a molecular study (ataxia telangiectasia mutated) to address whether there is a specific profile that increases toxicity risks. Results: We describe the design and implementation of this program, summary of previously published results, and ongoing research to influence stage at presentation. Some of the critical outcomes include the successful implementation of a community-based research program, development of trust within tribal communities, identification of barriers, analysis of nearly 400 navigated cancer patients, clinical trial accrual rate of 10%, and total enrollment of nearly 2,500 AIs on WF research studies. Conclusion: This NCI funded pilot program has achieved some initial measures of success. A research infrastructure has been created in a community setting to address new research questions and interventions. Efforts underway to promote cancer education and screening are presented, as well as applications of the lessons learned to other health disparity populations – both nationally and internationally.